Three-dimensional analysis of natural convection in nanofluid-filled parallelogrammic enclosure opened from top and heated with square heater - Al-Rashed, Abdullah A. A. A.; Hassen, Walid; Kolsi, Lioua; Öztop, Hakan Fehmi; Chamkha, Ali J.; Abu-Hamdeh, Nidal (Journal of Central South Univ, 2019)
A numerical study based on the finite volume method has been performed to study the three-dimension natural convection in a parallelogrammic top side opened cavity filled nanofluid with partially heated square at the bottom side. Results are obtained for different governing parameters such as nanoparticle concentration () from 0 to 0.05, inclination angle of the back and front walls () from 5 degrees to 75 degrees, Rayleigh number from 103 to 105, and length of heater changer from 0.1 to 1. The main finding from the obtained result showed that the inclination angle and nanoparticle volume fraction affect the flow structure and enhance the heat transfer.
Keywords: 3D analysis; open enclosure; partial heating; parallelogram; nanofluids